2021
DOI: 10.1101/2021.08.23.21262299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of nucleoporin Nup50 is a risk factor for amyotrophic lateral sclerosis

Abstract: The genetic basis of amyotrophic lateral sclerosis (ALS) is still incompletely understood. Using two independent genetic strategies, we show here that a large part of ALS heritability lies in genes expressed in inhibitory and excitatory neurons, especially at splicing sites regulated by a defined set of RNA binding proteins including TDP-43 and FUS. We conducted a transcriptome wide association study (TWAS) and identified 59 loci associated with ALS, including 14 previously identified genes, some of them not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 107 publications
2
6
0
Order By: Relevance
“…This finding is an important supplement to previous findings suggesting microglia (Clarke and Patani, 2020), astrocytes (Do-Ha et al, 2018;Saez-Atienzar et al, 2021), and glutamatergic neurons Cronin et al (2008) as the key cell types functionally involved in the development of ALS. Our finding on inhibitory neurons is highly consistent with a recent study, which showed that genetic variants associated with ALS were mostly located in genes expressed in neurons, particularly in inhibitory neurons, and ALS risk loci were significantly enriched in excitatory and inhibitory neurons using single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) profiles (Megat et al, 2021). It is known that inhibitory neurons release the neurotransmitter gammaaminobutyric acid (GABA) to regulate the initiation of excitatory neurons, ensuring our brain functions smoothly and accident-free (Foerster et al, 2013;Ramirez-Jarquin and Tapia, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is an important supplement to previous findings suggesting microglia (Clarke and Patani, 2020), astrocytes (Do-Ha et al, 2018;Saez-Atienzar et al, 2021), and glutamatergic neurons Cronin et al (2008) as the key cell types functionally involved in the development of ALS. Our finding on inhibitory neurons is highly consistent with a recent study, which showed that genetic variants associated with ALS were mostly located in genes expressed in neurons, particularly in inhibitory neurons, and ALS risk loci were significantly enriched in excitatory and inhibitory neurons using single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) profiles (Megat et al, 2021). It is known that inhibitory neurons release the neurotransmitter gammaaminobutyric acid (GABA) to regulate the initiation of excitatory neurons, ensuring our brain functions smoothly and accident-free (Foerster et al, 2013;Ramirez-Jarquin and Tapia, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…We compared the identified loci with the published TWASs and GWASs ( Supplementary Table S1 , p threshold < 5 × 10 −8 ), which was visualized with the R package “VennDiagram” ( Chen and Boutros, 2011 ). However, the latest TWAS ( Megat et al, 2021 ) was unavailable in the medRxiv and not included in the comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Other genes including CHRNA3, DAO, GLT8D1, SARM1, ARID1B, G2E3, TMEM175, USP35, PTPRN2, SLC9A8, and MAPKAPK3 seem to be peripheral and less relevant in ALS. It has been reported that some ALS genes are involved in proteostasis (including COPS7A, USP35, TMEM175, and G2E3), mitochondrial metabolism (including ATP5D, ATP5H, and BCS1L) or gene expression and RNA metabolism (including ATXN3, ARID1B, TAF10, and PTBP2), and that decreased expression of NUP50 (a constrained gene encoding a nuclear pore basket protein) was connected with ALS in a transcriptome-wide association study [ 32 ]. A recent study of the existing ALS-causing genes has highlighted the role of structural variants in ALS pathogenesis and shown that genomic structural variants in valosin-containing protein (VCP), C9orf72, and Erb-B4 receptor tyrosine kinase 4 (ERBB4) genes impacted the risk of developing ALS, its progression and survival, the site of onset as well as the age of incidence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genes implicated in ALS in humans and animal models were adapted from the literature without duplication, yielding a total of 76 genes. Forty eight genes ( ATXN2, ANXA11, ALS2, ATXN3, ANG, C9orf72, CHMP2B, CHRNA3, CHCHD10, DCTN1, DNAJC7, DAOEWSR1, ERBB4, FUS, FIG4, GLT8D1, GLE1, hnRNPA2B1, hnRNPA1, KIF5A, MATR3, NEK1, NIPA1, NEFH, OPTN, PON1, PON2, PON3, PFN1, PRPH, SOD1, SETX, SQSTM1, SARM1, SPG11, SIGMAR1, TARDBP, TBK1, TUBA4A, TIA1, TAF15, UNC13A, UBQLN2, VCP, VAPB, VEGF, and WDR7 ) were collected from Smukowski et al [ 8 ], 11 genes ( ARID1B, ATP5H, ATP5D, BCS1L, COPS7A, G2E3, NUP50, PTBP2, TAF10, TMEM175, and USP35 ) from Megat et al [ 32 ], 11 genes ( CFAP410 , COG3 , ERGIC1 , GPX3, TNIP1 , HLA, MOBP, RPSA , PTPRN2 , SLC9A8, and SPATA2 ) from van Rheenen et al [ 112 ], and 6 genes ( ACSL5 , ATG16L2 , MAPKAPK3 , MAP1LC3A , SCFD12 , and PLXNB ) from Saez-Atienzar et al [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…By using three TWAS methods (S-PrediXcan, UTMOST and JTI), we identified a total of 102 genes significantly associated with ALS by at least two methods (FDR < 0.05), of which 19 were reported in recent GWAS and post-GWAS studies ( 46 , 50 , 51 ) ( Supplementary Table S4 ), leaving a large number of newly identified candidate genes for ALS. By using the SMR analysis, we tested the exposure measurements from six types of cis-xQTLs and identified a total of 84 genes with significant evidence that likely mediated the genetic associations (FDR < 0.05 and HEIDI > 0.05).…”
Section: Database Content and Usagementioning
confidence: 99%